Use of Tasybih Verses in Surah Ar-Rahman as Teaching Material for Mahara Kalam in Arabic Language Learning - Martua Lubis, Muhammad Sholihin; Ritonga, Syaipuddin; Setiadi, Fadlan Masykura (Faidatuna, 2025)
Most people like surah Ar-Rahman when it is chanted. In surah Ar-Rahman there are tasybih which add to the beauty of the verse, Tasybih beautifies sentences when speaking, praising, or seducing. According to researchers, the beauty of prayer beads can increase a person's enthusiasm for learning Arabic, Because one of the reasons people don't want to learn Arabic is a lack of motivation. Using tasybih in Surah Ar-Rahman we can beautify our conversations in Arabic. The aim of this research is. Analyze the verses containing tasybih in Surah Ar-Rahman and their meaning. Analyze the various types of tasybih contained in Surah Ar-Rahman and their meanings. This type of research is library research, The data collection technique in this research is Documentation Technique, Data analysis : The researcher reads surah Ar-Rahman then collects verses containing tasybih and their types then prepares teaching materials from the tasybih. The results of the research found 4 verses containing tasybih, namely in verse.14,24,37,58. And 5 5 types of prayer beads, tasybih mufrad bil mufrad, tasybih, mufrad bil murakkab, mujmal, mursal dan muakkad. The connection between the tasybih verses in Surah Ar-Rahman and the mahara kalam is a semantic aspect. Because the tasybih in Surah Ar-Rahman can expand our knowledge about the meaning of sentences. Tasybih verses are interesting teaching materials to help students express their thoughts and feelings in Arabic.